Long-term exposure to PM2.5-bound metals and female breast cancer incidence in New Mexico, USA - Yanhong Huang; Charles L. Wiggins; Angela L. W. Meisner; Yan Lin; Li Luo; Xi Gong (Air Quality, Atmosphere & Health, 2026)
Abstract Female breast cancer (FBC) is the most commonly diagnosed malignant cancer and the second leading cancer cause of death among women in the United States. Environmental exposures, particularly PM 2.5 -bound metals, have been increasingly associated with breast cancer incidence. We evaluated associations between long-term residential exposure to PM 2.5 -bound metals and age-adjusted FBC incidence rate at the census tract level in New Mexico from 1997 to 2019. FBC records were obtained from the New Mexico Tumor Registry. Annual metal exposure intensities for chromium, cobalt, copper, manganese, and mercury were estimated using a calibrated Emission Weighted Proximity Model (EWPM) over a 10-year pre-diagnosis window. Generalized Estimating Equations (GEE) with Gaussian estimation was used to estimate rate ratio (RR) for the association between PM 2.5 -bound metal exposure and FBC incidence in New Mexico. Exposure to PM 2.5 -bound chromium (adjusted RR 1.07, 95% CI: 1.05, 1.08), cobalt (adjusted RR 1.08, 95% CI: 1.05, 1.11), copper (adjusted RR 1.06, 95% CI: 1.04, 1.07), manganese (adjusted RR 1.05, 95% CI: 1.02, 1.08), and mercury (adjusted RR 1.05, 95% CI: 1.03, 1.07) show significant associations with increased FBC incidence rate. When exposure was categorized as unexposed, low, medium, and high groups, a significant increasing trend was observed across all five metals. Long-term exposure to multiple PM 2.5 -bound metals is associated with elevated FBC incidence rate in New Mexico. These findings highlight the need for further research and to biologically validate the observed associations and clarify potential mechanisms linking PM 2.5 -bound metal exposure to FBC incidence risk.